Peter C. Petersen letter to Carl Bendorf regarding spring birding report for IOU quarterly field report spring 1991, May 31, 1991 - Petersen, Peter C.et al (1991)
Field reports submitted by Peter C. Petersen with several other observers with an introductory letter from Peter C. Petersen to Carl Bendorf on May 31, 1991. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1991. Epson - sheet feed/flatbed